(untitled) (Konferensiyalar | Conferences, 2024)
In today’s digitally-driven world, integrating Information and Communication Technology (ICT) and internet resources into primary education has become increasingly important. This article explores the benefits and challenges of utilizing ICT and internet information in reading lessons for primary classes. By examining various strategies, tools, and pedagogical approaches, this article aims to provide educators with insights into effectively incorporating technology and internet resources to enhance reading instruction in primary classrooms.